Macroeconomic-Driven Prepayment Risk and the Valuation of Mortgage-Backed Securities. (14th December 2017) - Chernov, Mikhail; Dunn, Brett R.; Longstaff, Francis A.
Abstract: We develop a three-factor no-arbitrage model for valuing mortgage-backed securities in which we solve for the implied prepayment function from the cross-section of market prices. This model closely fits the cross-section of mortgage-backed security prices without needing to specify an econometric prepayment model. We find that implied prepayments are generally higher than actual prepayments, providing direct evidence of significant macroeconomic-driven prepayment risk premiums in mortgage-backed security prices. We also find evidence that mortgage-backed security prices were significantly affected by Fannie Mae credit risk and the Federal Reserve's quantitative easing programs. Received May 10, 2016; editorial decision September 22, 2017 by Editor Stijn Van Nieuwerburgh.